When Online Exchanges Byte: An Examination of the Policy Environment Governing Cyberbullying at the University Level - Faucher, Chantal; Jackson, Margaret; Cassidy, Wanda (Canadian Journal of Higher Education, 2015)
This article reports on findings from a scan of 465 policies relevant to the handling of cyberbullying in 74 Canadian universities. It first assesses the commonalities and differences in the policies. Second, it considers how their various lenses—a human rights perspective versus a student conduct perspective, for instance—can affect the directions and outcomes of university responses. The majority of the policies reviewed were codes of student conduct and discipline, policies on electronic communication, and policies on harassment and discrimination. Most of the policies outlined complaint procedures and possible sanctions, but relatively few addressed prevention of unacceptable behaviours. Only about a third made reference to “cyber” behaviours, suggesting that the university policy environment is not current with the information and communication technologies that permeate the daily lives of university students and faculty.